Dame Mary Gilmore interviewed in the Hazel de Berg collection - Gilmore, Mary, Dame, 1865-1962.; De Berg, Hazel, 1913-1984. (1957)
Dame Mary Gilmore gives introductory remarks to her book "Old days, old ways" read for the "talking book" service for blind people ; Dame Gilmore reads two excerpts from her works.
Recorded by Hazel del Berg.
Digital master available
Transcripts available (1 p.+1p.)
Keywords: Australian poetry